Composition and surface chemistry engineering of graphene grafting chitosan for stimuli-responsive cancer therapy: An in-silico study. (2021) - Dahri, Mohammad; Abolmaali, Samira Sadat; Abedanzadeh, Mozhgan; Salmanpour, Mohsen; Maleki, Reza
Abstract: Purpose: Graphene-based drug delivery studies have been utilized in pharmaceutical science, primarily a molecular investigation of cancer therapy. The energetic interactions between drugs and graphene nanosheets are one of the critical components of cancer treatment studies. In the present work, Graphene-based nanosheets, including; carboxylated graphene (CGRA), Silicon-doped graphene (SiGRA) and Phosphorus-doped graphene (PGRA) were utilized as carriers for Doxorubicin/Paclitaxel co-delivery. Furthermore, these nanosheets were modified by pH- and thermal-sensitive co-polymer, named trimethyl chitosan (TMC)- b- N, N- dimethyl acrylamide (DMAA). TMC-DMAA co-polymer benefits from remarkable features leading to its pH- and temperature-sensitivity for drug loading and stimuli-responsive release purposes. Method: First, the TMC-DMAA co-polymer, as well as functionalized graphene molecules, have been optimized at acidic and neutral conditions. Then, the loading and release of drugs in the normal and cancerous conditions were investigated by molecular dynamics tools, respectively. Finally, the validation test clarified the accuracy and precision of the simulation systems. Results: The results indicated that TMC-DMAA functionalized graphene nanocarrier could retain drug molecules from unwanted interactions in normal tissues while causing the drug release in a pH and temperature-sensitive manner at the tumor microenvironment. Moreover, P-doped and Si-doped modification increased the capacity of drug loading on graphene nanosheets. Conclusion: By investigating molecular insight, shedding the light of anti-cancer drug loading and release achieved. The results of this study would help future studies about cancer drug delivery research. Graphical abstract: Image 1 Highlights: DOX and PAX co-delivery by functionalized graphene nanocarriers studied by molecular dynamics simulation. Van der Waals and electrostatic interactions and hydrogen bonds work throughout the combination. Effect of dimethyl acrylamide -trimethyl chitosan on the drug release kinetics is obtained via molecular dynamics. Drug release from the carboxylated graphene is controlled by the modifying polymer at various pH conditions. P-doped and Si-doped graphene increased the capacity of loading at normal condition.